2015
DOI: 10.3390/ijms161226100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Morphological and Cellular Events Underlying Oral Regeneration in the Sea Anemone, Nematostella vectensis

Abstract: Cnidarians, the extant sister group to bilateria, are well known for their impressive regenerative capacity. The sea anemone Nematostella vectensis is a well-established system for the study of development and evolution that is receiving increased attention for its regenerative capacity. Nematostella is able to regrow missing body parts within five to six days after its bisection, yet studies describing the morphological, cellular, and molecular events underlying this process are sparse and very heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 44 publications
7
104
0
5
Order By: Relevance
“…It was also evident that the 24 and 72 h expression profiles are more similar to each other than they are to 8 h (Fig. 2b), which is in line with previous studies defining the first 6–8 h as a distinct wound-healing stage [53, 57]. The similarity in the overall expression patterns of the two regions of regeneration, at each individual time point, suggests that a large part of the regeneration response is of a general nature which may govern general wound healing and tissue growth at large, and that side-specific differential expression patterns may be more limited.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It was also evident that the 24 and 72 h expression profiles are more similar to each other than they are to 8 h (Fig. 2b), which is in line with previous studies defining the first 6–8 h as a distinct wound-healing stage [53, 57]. The similarity in the overall expression patterns of the two regions of regeneration, at each individual time point, suggests that a large part of the regeneration response is of a general nature which may govern general wound healing and tissue growth at large, and that side-specific differential expression patterns may be more limited.…”
Section: Resultssupporting
confidence: 90%
“…1b). At 24 h we observed that the mesenteries seemed to be attached to the center of the cut area in both the oral and aboral fragments as reported before for oral regeneration [53, 57]. At 72 h tentacle buds can begin to be detected in the regenerating oral side, and in the regenerating physa the mesenteries appeared disconnected from the previously wounded area and the physal end is more rounded and clear.…”
Section: Resultssupporting
confidence: 80%
“…However, the expression of the classical mesodermal marker brachyury [82] in the central ring, as well as the activation of a MEK/ERK/ERG pathway (required for mesoderm formation in bilaterians [83]) in the central domain, provide additional compelling evidence that both domains together form sub-regionalized territories of the cnidarian endomesoderm. Tissue tracking experiments using photo-convertible fluorescent proteins [84] are required to determine the fate of the central domain and ring. It might also be important to carry out a precise physiological analysis of the differentiated tissues that originated from the endomesodermal territory, to gain more insight in the evolutionary origin of mesoderm in bilaterians.…”
Section: Discussionmentioning
confidence: 99%
“…The sea anemone Nematostella is emerging as a novel model of body regeneration (Amiel et al, 2015). Aldine Amiel (Röttinger laboratory, IRCAN, Nice, France) showed that tissue crosstalk between the mesenteries and the surrounding epithelia is required to induce a stem cell-based regenerative response, offering a new system to study cellular cooperation in tissue reprogramming.…”
Section: Model Systems To Study Stemness and Cellular Plasticitymentioning
confidence: 99%